Impact of Omnichannel Applications on Reuse Intention and Moderating Role of Personal Innovativeness and Habit in the Customer Journey - Alizada, Gadir; Huseynli, Bahman; Kandemir Çomoğlu, Gözde (International Review of Management and Marketing, 2026)
This research aims to examine the effects of omnichannel applications on the fast-food purchasing experience and the moderating role of personal innovativeness and habit on this experience. The study analyzed data collected from 418 Azerbaijani fast-food consumers using SPSS and Process v4. A total of nine hypotheses were developed and tested. The research study found that the sub-dimensions of the customer journey experience variable had a positive impact on reuse intention. Personal innovativeness was found to weaken the relationship between pre-purchase experience and purchase experience variables on reuse intention. Habit was found to weaken the purchase and post-purchase experience variables. One of the study’s most significant contributions is the finding that while personal innovativeness weakens consumers’ intention to reuse an existing brand due to their search for new experiences, habituation, resulting from consumers’ routine behavior, diminishes the impact of experience quality. This finding suggests the need to develop differentiated marketing and experience strategies targeted at different consumer profiles.